Dynamic crystallization during non-isothermal laser treatment of Fe–Si–B metallic glass. (16th November 2015) - Joshi, Sameehan S; Gkriniari, Anna V; Katakam, Shravana; Dahotre, Narendra B
Abstract: Fe–Si–B metallic glass foils were subjected to non-isothermal laser treatment to induce crystallization, and the effect of laser fluence on crystallite size was investigated. Temperature, and corresponding heating and cooling rates generated during laser processing of metallic glass were estimated using multiphysics computational models. Estimation of the onset and arrest temperatures of crystallization was based on the results obtained using the thermal model. Crystallite size was measured with the aid of x-ray diffraction and transmission electron microscopy. The fraction of crystallization was estimated with a differential scanning calorimetry. Crystallite size increased with laser fluence in the initial stages and saturated later within the laser fluence range (0.6–0.9 J mm −2 ) explored in the current efforts. The fraction of crystallization steadily increased with the increase in laser fluence. Unlike conventional processes, in the present situation the dynamic effects during laser processing dominated the crystallization and growth process. Rapid heating rates during laser processing led to a shift in the onset of crystallization temperature to a higher level. Faster cooling rates prematurely arrested the crystallite growth yielding much finer crystallite sizes.